Study of high-strength concrete beam-column joints with high-yield strength steel reinforcement - Abdul Naufal Abdol Jabar (2016)
This paper aims to study the behaviour of high-strength concrete beam-column joint reinforced using high-yield strength steel bar under seismic loading. An experimental study was first done using 4 interior beam-column joints constructed with materials of different grade strength and varying reinforcement detailing. The test revealed that using high-yield strength steel reinforcement bars together with high-strength concrete resulted in improving the load-carrying capacity of the tested specimens. A parametric study was also done via finite-element modelling (FEM) to supplement the experimental study. The parametric study showed that the models used behaved similarly to the tested specimens and thus can be safely used to predict beam-column joint behaviours when other parameters are varied.